Effect of Window Size on Residential Buildings’ Energy Costs - Telatar, Benihan; BOSTANCIOĞLU, ESRA (IDOSI Publications, 2013)
Today, with the rapid depletion of fossil energy sources and the increasing environmental problems caused by fossil fuels, supervision and management of energy consumption becomes more important. Looking at the breakdown of energy consumption by sectors, the buildings sector is seen as one of the priority areas for energy efficiency after industry and transportation. A large amount of energy is consumed during the utilization phase of the building. Therefore, priority is given to applications that reduce the amount of energy consumed during the utilization phase throughout the lifetimes of buildings. In the design phase, decisions regarding building window sizes have a considerable effect on the building energy costs. Therefore, this study will analyze the extent to which changes in building transparency rate affect building heating energy costs and thereby provide pre-design information for future reference for residential buildings with less energy consumption and less environmental pollution. To this end, residential buildings with the same characteristics have been used by differentiating only window sizes, orientations and envelope alternatives to assess the changes they cause in energy costs.
Keywords: Window size; Transparency rate; Energy efficiency; Envelope design; Energy cost